Pengaruh Beban Kerja dan Disiplin Kerja Terhadap Kinerja Karyawan pada Wisata Kampung Turis Karawang - Siti Elisah Widiah Astuti; Budi Rismayadi; Wike Pertiwi (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
This research aims to analyze the influence of workload and work discipline on employee performance at the Karawang Tourist Village Tourism. The research method used is a quantitative approach with a saturated sampling technique (Total Sampling), with a population of 56 employees. Data was collected using a questionnaire and analyzed using multiple linear regression. The research results show that workload does not have a significant influence on employee performance, with a regression coefficient value of -0.043 and a significance value of 0.741. Work discipline also has a significant effect on performance, with a regression coefficient of 0.242 and a significance value of 0.001. Simultaneously, workload and work discipline are able to explain 18.9% of the variation in employee performance. These findings emphasize the importance of measurable workload management and implementing a consistent culture of discipline to improve employee performance. This research provides recommendations for management to balance workload, strengthen a culture of work discipline, and pay attention to the balance between work and employees' personal lives in order to achieve optimal performance.